The symbolism of the lice in the Andean world. Philological sketch - Souffez, Marie-France (1985)
The value given to the lice varies according to the places and cultures of the world. In Peruvian urban areas it is synonymous of dirt and poverty. In traditional Andean rural areas, it seems to us to be associated with poverty and wealth, death and life. The modalities and the nuances of expression of these associations form the object of our study. This article develops a partial analysis of the Quechua and Aymara vocabulary related to this parasite.